Ontogenetic development of the sagittal otoliths of the anchovy, Anchoa tricolor (Spix and Agassiz, 1829), in a subtropical estuary - Maichak de Carvalho. Barbara (2015)
In order to characterize the ontogeny of Anchoa tricolor, the morphology and morphometry of sagitta otoliths were described. A total of 397 pairs of sagitta otoliths of A. tricolor (20 to 85 mm) were measured and analysed by means of digital images. Morphological description was done in terms of shape and features. The Huxley model was fitted to otolith length against total length (TL) and weight (TW), and residual analyses were done in order to detect the polyphasic growth. Six shape indices were calculated (otolith height/otolith length and otolith length/total length aspect ratios, rectangularity, roundness, relative sulcus surface and rostrum index) and after size effect removal, they were analysed in terms of TL. The results of these analyses allowed three distinct growth phases to be identified: (1) up to 40 mm TL and related to low swimming ability; (2) between 41 and 60-70 mm TL, when fish displacements increase but the first maturation has not yet occurred; and (3) after 71 mm TL, when fish become adults. Landmarks and semi-landmarks were used to analyse relative warps during the otolith development. The MANOVA analysis between the centroid size and class intervals showed significant differences in the interaction of all classes except between 71-80 and 81-90 mm.